(untitled) (Research, Society and Development, 2020)
Faced with the challenges of teaching Science, interdisciplinarity emerges as an integrative teaching proposal in order to enable mediation of content, facilitating the teaching and learning process. Despite their importance and references in the different legal documents that regulate and guide Basic Education, integrating methodologies are still little explored. After the reformulation in 2009, the National High School Examination proposes interdisciplinarity between the different areas of education. Thus, this research aims to analyze the articulation of the concepts of Mathematics present in the questions of Biology in the ENEM tests from 2010 to 2019, verifying the level of interdisciplinarity and contextualization present in these questions. Data collection took place through bibliographic analyzes, with a quantitative and descriptive approach. All Biology questions applied at Enem from 2010 to 2019 were analyzed. It is noted that there is an interdisciplinary and contextual articulation between Mathematics and Biology, even though this number is decreasing over the years of the exam applications.